2003
DOI: 10.1016/j.pain.2003.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome domains for chronic pain clinical trials: IMMPACT recommendations

Abstract: There was a consensus that chronic pain clinical trials should assess outcomes representing six core domains: (1) pain, (2) physical functioning, (3) emotional functioning, (4) participant ratings of improvement and satisfaction with treatment, (5) symptoms and adverse events, (6) participant disposition (e.g. adherence to the treatment regimen and reasons for premature withdrawal from the trial). Although consideration should be given to the assessment of each of these domains, there may be exceptions to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
836
1
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,958 publications
(888 citation statements)
references
References 32 publications
18
836
1
15
Order By: Relevance
“…Therefore, the findings of the present study should be further confirmed in future prospective studies that use psychometrically well-defined instruments that have been validated for the assessment of each specific pain rather than for assessment of overall pain. Consistent with the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials recommendations [63], future studies should also consider including an expanded assessment of pain interference and emotional function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings of the present study should be further confirmed in future prospective studies that use psychometrically well-defined instruments that have been validated for the assessment of each specific pain rather than for assessment of overall pain. Consistent with the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials recommendations [63], future studies should also consider including an expanded assessment of pain interference and emotional function.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, the primary and secondary endpoints addressed all recommended outcome domains for chronic pain trials 6 .…”
Section: Discussionmentioning
confidence: 99%
“…We also aimed to assess whether these behavioral responses mediated the relation between partner cognitions, pain, and depressive symptoms. Depressive symptoms have previously been shown to be more elevated in the PVD population and is an important painrelated outcome 20,38 One such relevant partner cognition is catastrophizing. Greater spousal catastrophizing has been associated with more patient pain in chronic pain and PVD samples [21][22][23] , but the mechanism underlying this relationship has not been investigated.…”
Section: Introductionmentioning
confidence: 99%